PENANAMAN KARAKTER NASIONALISME MELALUI PEMBELAJARAN MULOK BAHASA JAWA BANTEN DI KELAS V SDN CIPOCOK JAYA 2 - Listiana, Mina; Setiawan, Sigit; Fajrudin, Lili (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to examine the planning and implementation of local content learning in Banten Javanese language in fostering nationalism character among fifth-grade students at SDN Cipocok Jaya 2, as well as the outcomes of the learning process. The research employed a descriptive method with a qualitative approach, involving fifth-grade students as the subjects. Data were collected through interviews, observations, and documentation. Data analysis followed Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The results showed that: (1) teachers’ lesson planning in fostering nationalism character was carried out by designing teaching plans and determining strategies to instill such values; (2) the implementation required teachers to organize active student participation, integrate Banten Javanese language materials with nationalism values, utilize learning resources and media, and demonstrate strong subject mastery; and (3) nationalism character values were successfully instilled and sufficiently demonstrated by the students. In conclusion, the integration of local content learning with character education effectively supports the development of nationalism among elementary school students.